Respiratory Care Considerations for Children with Medical Complexity - Jackie Chiang; Reshma Amin (MDPI AG, 2017)
Children with medical complexity (CMC) are a growing population of diagnostically heterogeneous children characterized by chronic conditions affecting multiple organ systems, the use of medical technology at home as well as intensive healthcare service utilization. Many of these children will experience either a respiratory-related complication and/or they will become established on respiratory technology at home during their care trajectory. Therefore, healthcare providers need to be familiar with the respiratory related complications commonly experienced by CMC as well as the indications, technical and safety considerations and potential complications that may arise when caring for CMC using respiratory technology at home. This review will outline the most common respiratory disease manifestations experienced by CMC, and discuss various respiratory-related treatment options that can be considered, including tracheostomy, invasive and non-invasive ventilation, as well as airway clearance techniques. The caregiver requirements associated with caring for CMC using respiratory technology at home will also be reviewed.